Modulation of CD103 expression on human colon carcinoma-specific CTL. - Ling, K; Dulphy, N; Bahl, P; Salio, M; Maskell, K; Piris, J; Warren, B; George, B; Mortensen, N; Cerundolo, V (2007)
Recent results have shown a correlation between survival and frequency of tumor-infiltrating T cells in colorectal cancer patients. However, the mechanisms controlling the ability of human T lymphocytes to infiltrate colon carcinoma remain unclear. Although, it is known that expression of the integrin CD103alpha(E)/beta(7) by intraepithelial lymphocytes controls the retention of lymphocytes in epithelial layers, very little is known about the expression of intestinal homing receptors in human T lymphocytes. In particular, it remains unknown whether expression of CD103/beta(7) by human colon cancer-specific T lymphocytes is controlled by recognition of tumor Ags and is imprinted during T cell priming, facilitating its expression during memory T cell activation. In this study, we demonstrate that expression of CD103/beta(7) in human colon carcinoma-specific CTL is synergistically enhanced by the simultaneous TGF-beta1 stimulation and Ag recognition. These results were confirmed by using a panel of human CTL clones. Finally, we show that priming of naive CD8(+) T cells in the presence of TGF-beta1 ensures up-regulation of CD103/beta(7) in recall responses, at concentrations of TGF-beta1 significantly lower than those required by memory T cells primed in the absence of TGF-beta1. These results indicate a role of TGF-beta1 during T cell priming in modulating expression of CD103/beta(7) and controlling retention of human memory CD8(+) T cells into tumor epithelium.